Microirrigation for sustainable production of pomegranates - Meshram, D T; Singh, N V; Pal, R K (Indian Horticulture, 2019)
Water is the most critical input for enhancing pomegranate productivity, and therefore, expansion of microirrigation has been a key strategy in maximization of pomegranate production. Microirrigation has the potential to use scarce water resources most efficiently to give high returns. The major benefits of microirrigation are ability to apply low volumes of water to plant roots, reduced evaporational losses and improved irrigation uniformity. Microirrigation applies water below and above the soil surface, using buried and non-buried laterals with inline and online drippers. The biophysical advantages are lower canopy humidity, water saving and fewer diseases and weeds. The yield and quality of pomegranates can be improved with subsurface drip irrigation system as compared to surface drip irrigation system.